Pengaruh E-Recruitment, Reputasi Perusahaan, dan Kompensasi terhadap Minat Melamar Pekerjaan pada Mahasiswa Universitas Perwira Purbalingga - Lutfy Ike Prasetyawati; Dyah Supriatin (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Final-year students have a high interest in immediately entering the workforce, but the available recruitment processes often do not meet their expectations. The e-recruitment system, which is expected to be efficient and transparent, instead causes confusion and doubt. Company reputation and compensation offered are also major considerations in the decision to apply. This study aims to analyze the influence of e-recruitment, company reputation, and compensation on the interest of Perwira Purbalingga University students in applying for jobs. A quantitative method was used with a causal associative approach. A sample of 59 respondents was selected through purposive sampling from students enrolled in 2021 and 2022. Data collection was conducted through questionnaires, then analyzed using instrument testing, descriptive analysis, classical assumption testing, and multiple linear regression. The results showed that e-recruitment had a negative and insignificant effect on job application interest. Company reputation had a positive and significant effect, while compensation had a positive but insignificant effect. The coefficient of determination value of 0.319 indicates that the three variables explain 31.9% of the variation in interest in applying for jobs, while the rest is influenced by other factors not examined in this study